2011
DOI: 10.1523/jneurosci.0577-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Confers Stress Resiliency to Social Defeat through an Infralimbic Cortex-Dependent Neuroanatomical Pathway

Abstract: Enriched environmental (EE) housing dampens stress-induced alterations in neurobiological systems, promotes adaptability, and extinguishes submissive behavioral traits developed during social defeat stress (SD). In the present study, we hypothesized that enrichment before SD can confer stress resiliency and, furthermore, that neuronal activity in the prefrontal cortex (PFC) is requisite for this resiliency. To test these hypotheses, mice were housed in EE, standard (SE), or impoverished (IE) housing and then e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
182
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(203 citation statements)
references
References 62 publications
15
182
2
4
Order By: Relevance
“…Based on the present study, we hypothesize that an enhanced capability of the infralimbic cortex to control the HPA axis contributes to the resilience of enriched animals to stress. In support of this hypothesis, it has been shown that EE increases the resilience of animals to social defeat stress by enhancing infralimbic cortical outputs to downstream limbic areas [9]. Also, in line with this possibility, it has been shown that an increased excitability in the PFC is associated with enhanced control over stress [33] and extinction learning [31].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Based on the present study, we hypothesize that an enhanced capability of the infralimbic cortex to control the HPA axis contributes to the resilience of enriched animals to stress. In support of this hypothesis, it has been shown that EE increases the resilience of animals to social defeat stress by enhancing infralimbic cortical outputs to downstream limbic areas [9]. Also, in line with this possibility, it has been shown that an increased excitability in the PFC is associated with enhanced control over stress [33] and extinction learning [31].…”
Section: Discussionmentioning
confidence: 74%
“…These behavioural effects produced by environmental enrichment (EE) are, in part, mediated by changes in the activity of the HPA axis and the release of corticosterone [24]. Studies from our laboratory and others suggest that changes in the activity of the PFC, presumably infralimbic cortex, explain the reduced reactivity to stress that is observed in enriched animals [9,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the infralimbic subregion of the mPFC is required for stress resiliency conferred by environmental enrichment that suppresses induction of depressive and anxiety-like behaviors by repeated stress (6). The rapid antidepressant action of ketamine also requires the mTOR pathway in the mPFC (7).…”
Section: A Role For the Mpfc In Depressive Behaviors Induced By Repeamentioning
confidence: 99%